Modelling, Simulation and Validation for a Multimode Double-Pendulum Overhead Crane - Sharifah Yuslinda Syed Hussien; Hazriq Izzuan Jaafar; Rozaimi Ghazali; Mariam Md Ghazaly; Mohd Khairul Azizat Johari; Liyana Ramli (ARQII Publication, 2024)
Indexed by Scopus